PENGEMBANGAN POTENSI DESA DAN PENINGKATAN PENGELOLAAN HASIL TAMBAK MELALUI KKN TEMATIK DI DESA ALUE DUA MUKA O, ACEH TIMUR UDUL - Yusri Nadya; Nurlaila Handayani; Yusnawati; Ipak Neneng MB; Rasidin; Hayatun Nufus; Awalu Rahman; Siti Juleha; Teuku Syahrizal; Iqbal Pamungkas; Ahmadi Sutrisna; Nurliana Dalimunthe; Elviana; Ramaidani; Siti Latifah (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
Thematic Community Service (Kuliah Kerja Nyata or KKN) is a form of student engagement with the community, focusing on social issues and development in specific areas. This article discusses the Thematic KKN program by the Faculty of Engineering at Samudra University in Alue Dua Muka O Village, East Aceh, which aims to develop the village's potential, address various issues, and enhance students' soft skills. The village relies on the fishing sector and fish and shrimp pond farming, but faces various challenges such as declining pond production, poor coastal conditions, limited government and community involvement, unclear pond mapping, low-quality marketing, and dependence on direct sales. Therefore, this KKN program aims to improve the community's well-being through better pond management, training in producing processed products, making natural fish feed, technology awareness, aerator machine maintenance, pond mapping, and sales profit analysis. The program's achievements show an increase in the community's understanding and skills in pond management, product marketing, and aerator machine maintenance. This article covers implementation methods, identified issues, work programs, and program achievements. The Thematic KKN program's goal is to make a positive contribution to the community in Alue Dua Muka O Village.